QUALITY OF SURFACE AND UNDERGROUND WATER IN THE AREA OF INFLUENCE OF A GYPSUM QUARRY IN PERU - Barriga Paria, Christ Jesus (2022)
This paper shows a study of the physicochemical parameters to determine the quality of groundwater and surface water in the area of influence of a gypsum quarry in Peru. The evaluation was carried out based on the Environmental Quality Standards (ECAs) for water approved by Supreme Decree No. 004-2017-MINAM, specifically for Category 3 - D1 (vegetable irrigation) and for Category 3 - D2 (animal drink). For the analysis of groundwater quality, 1 point corresponding to an artisanal well located in the area of La Alameda was sampled. For the analysis of surface water, the sampling network was carried out in springs, surface flow and water stagnation, which were found in two areas, within the concession under study and surroundings. To determine the reliability of the chemical analysis, an ionic balance of the main cations and dissolved anions was performed. In addition, to characterize the surface waters, the Piper Diagram and the Stiff Diagram were used, resulting in the predominance of calcium sulfated waters. Groundwater turned out to be slightly acidic and surface water slightly alkaline with significant sulphate concentration values.